Media attention on inflation - Gabrovšek, Nik (knjige, 2026)
This paper examines the media attention on inflation in Slovenia through time, with the special focus on the post-pandemic period. We construct an Inflation Attention Index using textual analysis of more than 600,000 Slovenian news articles published between 1997 and 2025 and collected through web scraping. We document three key findings. First, the surge in inflation was accompanied by a more than fourfold in-crease in media attention relative to its pre-pandemic level, with attention remaining elevated even as headline inflation converged to the policy objective. Second, the as-sociation between inflation and inflation attention strengthened in the post pandemic period, suggesting stronger correlation in high inflation environments. Third, inflation coverage was dominated by food related topics, while energy prices, trade develop-ments and financing conditions also contributed to inflation discourse. The persistent-ly elevated inflation attention in the post-pandemic period is particularly relevant in the context of heightened risks to (de )anchoring of inflation expectations and stronger and longer-lasting pass through of macroeconomic shocks to inflation.
Keywords: cene; ekonomski kazalci; elektronske knjige; energetika; pandemija; živila